Orom Sasadu: Hakikat dan Maknanya Bagi Masyarakat Suku Sahu Di Halmahera Barat, Maluku Utara - Nanuru, Ricardo Freedom (Jurnal Filsafat "WISDOM", 2019)
Indonesia has a variety of dining customs. Traditions that can be mentioned, among others Makan Patita in Ambon, Makan Basamo in Padang, Megibung in Bali, Bancakan in Bandung, and Orom Sasadu in Sahu, West Halmahera. This paper aimes to raise the meaning in the traditional dining custom (Orom Sasadu) organized by the Sahu tribe community in West Halmahera, North Maluku. This paper uses a qualitative approach that describes Sasadu's cultural background in Sahu including Orom Sasadu tradition and explores the meaning contained in it. This paper will begin with a general description of the area of West Halmahera where the Sahu tribe lives, be followed by Sasadu's historical background as a traditional house which is the characteristic of the Sahu culture, Sasadu’s architecture, and put forward a few point of views on dining together in a cultural perspective to enrich the paper, and be ended by presenting the Orom Sasadu tradition or traditional dining custom held in Sasadu and its meaning for the Sahu tribe community. This paper concludes that the Sasadu Orom tradition has at least 5 (five) meanings, such as: becoming a venue for enforcing rules that culminate in peace; reinforcing social relations of brotherhood; strengthening the protecting social structure; becoming moral education for the community; and reinforcing the pattern of human relations, especially the Sahu tribe community with its natural environment.